The Interactive influence between sex and probiotic on whole period’s broiler using non-linear pattern and in vivo experiment - Danung Nur Adli; Gallusia Marhaeny Nur Isty (Jurnal Nutrisi Ternak Tropis, 2022)
The interactive influence between sex and probiotic on whole period’s broiler using non-linear pattern and in vivo experiment; curve growth performance, relatively organ weight of broiler was investigated. First experiment were day-old-chicks of Ross 308 placed among control and experimental. The first experiment were used 56 Ross 308 broiler with aged 35 days including 28 males and 28 females as control, and 28 males and 28 females supplemented with or without probiotics. The second experiment were used non-linear models of Gompertz models to predict between sex and probiotic effect on the growth performance. The data analyses were uses two-way of variance between probiotic and sex (male-female). At the end experiment (35 aged d) thus probiotic and sex were significant difference (p > 0.05) on live weight (g), feed intake (g). To sum up, the interaction between group × sex was significant for body weight (g) broiler and non-linear models were effective to comparison between in vivo and predicted models.